2021
DOI: 10.3390/joitmc7010068
|View full text |Cite
|
Sign up to set email alerts
|

Industry 4.0: A Technological-Oriented Definition Based on Bibliometric Analysis and Literature Review

Abstract: Industry 4.0 was introduced in 2011 and since then has been perceived in multiple ways such as a vision, a paradigm, a scenario or as a digital revolution in production and service organizations. Even though Industry 4.0 is associated with great improvements for companies, there is still a lack of a uniform definition of the term Industry 4.0, especially when it comes to the transfer of knowledge from theoretical research to the implementation in organizations, which leads to confusion and disaffirmation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 125 publications
0
24
0
Order By: Relevance
“…This article has explored this WoS and Scopus database, the largest, oldest indexing databases [35], they are widely utilized in several review articles [36,37].…”
Section: Methodsmentioning
confidence: 99%
“…This article has explored this WoS and Scopus database, the largest, oldest indexing databases [35], they are widely utilized in several review articles [36,37].…”
Section: Methodsmentioning
confidence: 99%
“…Industry 4.0, which emerged in Germany between 2011 and 2015, is based on the three previous revolutions, i.e., machines, automation, systematization, and data processing. Specifically, I4.0 integrates the elements of the physical context with those of cyberspace [11]. However, it is still in the process of development and is still manifesting itself as a paradigm for the productive processes of the economy, companies, and countries [12].…”
Section: Fourth Industrial Revolutionmentioning
confidence: 99%
“…He found high coherence of price movement in Euro, British pound, and Renminbi currencies and eleven major cryptocurrencies with coronavirus panic index. Rupp et al (2021) examined the co-movement between 'Dow Jones World Stock Market' and 'Sukuk Market' along with 'Islamic Stock Market' with the help of wavelet transformation technique suggested that in comparison of short-term, long-term portfolio diversification gives benefits. Disli et al (2021) examined the correlation among safe-haven financial assets, i.e., gold crude oil and cryptocurrencies, with the help of wavelet coherence analysis.…”
Section: Review Of Literaturementioning
confidence: 99%